Persistent depressive symptom trajectory is associated with cognitive impairment: a population-based longitudinal study of aging in Taiwan - Hsiao-Chen Lin; Wai-Lam Lao; Te-Chia Tseng; Chih-Jung Yeh (BMC Geriatrics)
Abstract Background To investigate the associations between five depressive symptom trajectories and cognitive impairment in Taiwan’s older population. In addition, we investigated the moderating factors influencing these associations. Methods This population-based, longitudinal, cohort study was conducted on the basis of the Taiwan Longitudinal Study on Aging. Data corresponding to the fifth (2003), sixth (2007), and seventh (2011) survey waves were analyzed, focusing on individuals aged ≥ 65 years. Depressive symptom trajectories were analyzed using the 10-item Centre for Epidemiological Studies Depression scale, and cognitive function was assessed using the Short Portable Mental State Questionnaire. Logistic regression models were adjusted for various covariates such as sociodemographic, lifestyle, and health-related variables. We also investigated moderating effects of sex, age, type 2 diabetes mellitus, hypertension, and coronary heart disease. Results Five trajectories of depressive symptoms included 1,549 older individuals were identified. Approximately 36.09%, 47.13%, 5.68%, 6.20%, and 4.91% exhibited no, mild, decreasing, increasing, and persistent depressive symptom trajectories, respectively. The odds ratios for cognitive impairment were 3.17 (95% confidence interval [CI]: 1.41–7.15) in Model 1; 3.24 (95% CI: 1.42–7.41) in Model 2; and 2.95 (95% CI: 1.24–7.00) in Model 3 in individuals with persistent depressive symptom trajectory. Only persistent depressive symptom trajectory reached statistical significance in all three models. Cognitive decline was evident across all trajectories. The rate of cognitive decline was more rapidly in the persistent depressive symptom trajectory, nearly twofold to no depressive symptom trajectory, which the corresponding β values (score/year) were − 0.0862, − 0.1020, − 0.1192, − 0.1206, and − 0.1683 for the no, mild, decreasing, increasing, and persistent depressive symptom trajectories, respectively. Female sex, older age, type 2 diabetes mellitus, and coronary heart disease were significant moderators on the risk of cognitive impairment. Discussion Persistent depressive symptoms is associated with cognitive impairment in older adults. Identifying high-risk subgroups is crucial for targeted assistance. Policymakers and health-care professionals should be informed accordingly.